COMPOSITE MIXTURES BASED ON SYNTHETIC POLYMERS AND FILLERS AND EQUIPMENT FOR 3D PRINTING WITH THEM - POLISHCHUK, ANDRII; POLISHCHUK, OLEH; LISEVICH, SVITLANA; URBANIUK, YEVHEN; RUBANKA, MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article states that the use of composite materials instead of traditional materials allows you to significantly reduce the weight of the product, while not changing the strength characteristics of this material. It was determined that polymer composite materials based on metal powders, high-strength organic (aramid) and carbon fiber fillers with a polymer matrix are promising for use as structural materials. Fillers are used to improve the operational properties of the composite material (strength, stiffness, heat resistance), give them various specific properties and reduce the cost. The classification of polymer composite materials by matrix and filler is presented. It is noted that the greatest variety of properties can be obtained using solid fillers of different nature (metals, ceramics, polymers) and structures. It has been established that both the type of filler and the shape and size of the particles are important when forming certain properties of polymer composite materials. It was determined that composite materials are used in additive technologies, in particular in 3D printing. Examples of the production of composite filaments by various companies, including various types of fillers, are given. The developed technology of printing with a mixture of polymer connector and filler using a 3D printer, which includes certain stages, is presented. Polymer materials and solid fillers of various nature were selected as the matrix for experimental research and their properties were described. The classification of equipment for forced mixing of materials is described. The developed extruder that prints with granules or composite mixtures of polymer materials and the 3D printer on which it is installed are presented. Composite mixtures for conducting experimental studies are given. The parameters of the printed samples to be examined are specified.